DIGITAL MARKETING TECHNIQUES LEVERAGING SOCIAL MEDIA: DRIVING TANGIBLE BUSINESS OUTCOMES (IITM Journal of Business Studies, 2025)
he effectiveness of digital marketing strategies  in boosting online business sales through social  media platforms is a critical area of study in  today’s digital age. This research aims to delve  deeply into how businesses can leverage social  media for marketing purposes to enhance  their sales performance. Digital marketing has  become indispensable for businesses aiming to  reach and engage with their target audiences  effectively. Social media platforms, such as  Facebook, Instagram, Twitter, LinkedIn,  and others, have emerged as powerful tools  for marketers because of their extensive user  bases and advanced targeting capabilities.  These platforms enable businesses to create  targeted advertising campaigns, share engaging  content, interact directly with customers, and  leverage influencer partnerships to increase  brand visibility and drive sales. This research  serves as a comprehensive guide for businesses seeking to harness the power of social media  to increase their online sales through effective  digital marketing strategies. By synthesizing  theoretical knowledge with empirical findings,  this study provides actionable insights and  best practices that businesses can implement  to optimize their digital marketing efforts,  maximize revenue generation, and cultivate  long-term customer relationships in the digital  era.
Keywords: Digital marketing; Social media marketing; Online sales, Revenue generation; Social media platforms; Marketing tactics; Consumer engagement; Business growth; Empirical analysis